Factors Influencing the Research Participation of Adults with Autism Spectrum Disorders - Haas, K.; Costley, D.; Falkmer, Marita; Richdale, A.; Sofronoff, K.; Falkmer, Torbjorn (2016)
Recruiting adults with autism spectrum disorders (ASD) into research poses particular difficulties; longitudinal studies face additional challenges. This paper reports on a mixed methods study to identify factors influencing the participation in longitudinal autism research of adults with ASD, including those with an intellectual disability, and their carers. Common and differentiating factors influencing the research participation of participants are identified and discussed. Factors influencing participation were found to differ both between and within participant categories. We propose a dichotomy whereby factors influencing research participation can be classified as those arising from a participant’s values, which act as either a motivator or a deterrent; and those based on convenience, which act as either an enabler or inhibitor. These findings are applicable to research studies that seek to recruit adults with ASD as participants.